Customer Satisfaction with Mobile Banking Services in Nepalese Commercial Banks - Goet, Joginder; Kharel, Kiran (Management Dynamics, 2022)
This study aims to examine the effects of convenience, communication, time-saving, and security on how satisfied customers are with Nepalese commercial banks’ mobile banking services. The study used a descriptive and causal-comparative research design to estimate the relationship between customer satisfaction and the convenience, communication, time-saving, and security factors affecting customer satisfaction with mobile banking. The research depends on the information obtained from a self-administered questionnaire survey. Four hundred twenty questionnaires were issued to the customers of 21 commercial banks, and 395 questionnaires were eventually gathered for analysis. The findings show a positive and significant correlation between convenience, communication, time-saving, and security with customer satisfaction. Convenience, communication, and time-saving significantly and positively impact customer satisfaction, and security does not affect customer satisfaction. This study is helpful for Nepalese Commercial Bank management who desire to manage their mobile banking services efficiently.